2003
DOI: 10.1093/brain/awg273
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal associative plasticity of the human motor cortex in writer's cramp

Abstract: Low-frequency median nerve stimulation, paired with suprathreshold transcranial magnetic stimulation (TMS) over the optimal site for activation of the abductor pollicis brevis (APB) muscle induces a long-lasting increase in the excitability of corticospinal output neurons, if median nerve stimulation is given 25 ms before TMS. Here we employed this protocol of stimulation to assess associative plasticity of the primary motor hand area in 10 patients with writer's cramp and 10 age-matched controls. Motor evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
284
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(319 citation statements)
references
References 50 publications
27
284
2
6
Order By: Relevance
“…1). Large response variability has also been reported in the PAS literature with MEP amplitude increases ranging from 32% [7] to 79% [23] and response rates as low as 50% [31]. In the current study, we report a (nonsignificant) 50% increase in MEP amplitude following PAS and a response rate of 67%, a result that falls well within the range of PAS-induced MEP facilitation reported by others.…”
Section: Discussionsupporting
confidence: 90%
“…1). Large response variability has also been reported in the PAS literature with MEP amplitude increases ranging from 32% [7] to 79% [23] and response rates as low as 50% [31]. In the current study, we report a (nonsignificant) 50% increase in MEP amplitude following PAS and a response rate of 67%, a result that falls well within the range of PAS-induced MEP facilitation reported by others.…”
Section: Discussionsupporting
confidence: 90%
“…Impaired PAS-induced LTP-like plasticity is typically observed in disorders associated with a dysfunctional dopaminergic system such as Parkinson's disease (Morgante et al, 2006;Ueki et al, 2006;Schwingenschuh et al, 2010) or schizophrenia (Frantseva et al, 2008), or a deficient central cholinergic system such as Alzheimer's disease (Battaglia et al, 2007), whereas exaggerated PASinduced LTP-like plasticity can be observed in states of increased endogenous central cholinergic tone such as dystonia (Quartarone et al, 2003(Quartarone et al, , 2008Weise et al, 2006;Schwingenschuh et al, 2010).…”
Section: Clinical Perspectivementioning
confidence: 99%
“…The assumption underlying PAS effects is that nerve stimulation and the TMS pulse both evoke inputs onto a common neuronal population that ultimately demonstrates short-term associative synaptic plasticity due to the repeat pairing of separate inputs. Following PAS protocols in uninjured individuals, increases in MEP amplitude [87] and cSP [90] are observed. PAS-induced increases in corticospinal excitability are mediated by glutamate and are blocked in the presence of NMDA receptor antagonists [89].…”
Section: Paired Associative Stimulation (Pas)mentioning
confidence: 98%